Implementation and product- and process evaluation of a co-created gender-informed and culturally-sensitive toolkit to improve symptom recognition and care seeking for ischemic heart disease: RE-AIM framework - Bryn Hummel; Dinah L. van Schalkwijk; Nina Zipfel; Pearl T. C. Tuithof; Paula M. C. Mommersteeg; Ralf E. Harskamp; Irene G. M. van Valkengoed (PLoS ONE, 2026)
Background Tailored health messaging can be used to improve symptom recognition of ischemic heart disease (IHD) and reduce barriers to care. Therefore, we propose that a gender-informed and culturally-sensitive toolkit for health messaging could improve health outcomes by promoting adequate care seeking in the community. Hence, we will develop, implement, and evaluate a toolkit to improve IHD-related symptom recognition and care seeking in an ethnically-diverse population. Methods We developed a toolkit in co-creation with patients, citizens, community leaders, and healthcare professionals. Subsequently, we pilot-implemented the toolkit through organizing information sessions in four different community-based settings. Finally, using a mixed-methods design, we evaluated the Reach, Effectiveness, Adoption, Implementation, and Maintenance of the toolkit (RE-AIM), including its effect on knowledge gain on symptom recognition and care seeking,. Results Approximately 240 people attended the information sessions, of whom 69% women, and the mean age was 63 (standard deviation 10.7) years old. Our results showed a small increase [varying from 53.4–74.4% pre-test to 67.6–85.4% post-test] in knowledge about IHD symptoms. A great willingness to adoption the intervention was observed among the targeted community leaders, and despite several points of improvement, including fidelity to the implementation, attendees and community leaders reflected positively on the toolkit. The main challenge regarding the maintenance of the toolkit was a lack of experience in organizing community events by potential maintenance organizations. Conclusion While the co-created toolkit was well-received, and findings concerning the reach, adoption, and implementation were positive, the (cost)effectiveness should be further evaluated to study the long-term impact of the intervention. Moreover, the need for integration of the intervention in current infrastructure constituted a challenge to the maintenance of the toolkit.